Sugemule-7 alleviates oxidative stress, neuroinflammation, and cell death, promoting synaptic plasticity recovery in mice with postpartum depression - Qiang Fu; Rui Qiu; Jiaquan Liang; Shuai Wu; Dezhi Huang; Yuxiang Qin; Qiaosheng Li; Xiaojie Shi; Xiyue Xiong; Zhongyong Jiang; Yuewen Chen; Yong Cheng (Scientific Reports)
Abstract Postpartum depression (PPD) profoundly impacts the mental and physical health of women globally and is an incurable psychological disorder. Traditional pharmacological treatments often have strong side effects and may adversely affect infant health through breastfeeding, underscoring the critical need for natural and gentle treatment strategies. Sugemule-7, a traditional Chinese medicine comprising multiple natural plant ingredients, represents a potentially safer and more effective alternative. To investigate its preventive effects on PPD, we established an animal model and administered the drug Sugemule-7. Our study demonstrated that varying doses of Sugemule-7 effectively alleviated depressive and anxiety-like behaviors in PPD mice, as assessed through a battery of tests, including the open field test, tail suspension test, sucrose preference test, forced swim test, novelty-suppressed feeding test, and elevated plus maze test. Furthermore, Sugemule-7 significantly improved oxidative stress levels in the serum, prefrontal cortex, and hippocampus of PPD-induced mice while also suppressing inflammatory responses and abnormal neuronal death in these brain regions. Transcriptomic sequencing of hippocampal and prefrontal cortex tissues supported our findings, revealing that differential gene expression is primarily involved in regulating synaptic plasticity. Overall, our study confirms the efficacy of Sugemule-7 in treating PPD at different concentrations, potentially alleviating depressive behaviors by enhancing synaptic plasticity, mitigating oxidative stress, reducing inflammation, and protecting neurons.